Permanences de la révolution : pour un autre bicentenaire. - Balibar, Etienne; Bensaïd, Daniel; Löwy, Michael; Toussaint, Eric (Montreuil : La Brèche-PEC, 1989)
Bibliotheek François Vercammen
Frans
Monografie